Application of a Reverse Genetic System for Beet Necrotic Yellow Vein Virus to Study Rz1 Resistance Response in Sugar Beet - Liebe, Sebastian; Wibberg, Daniel; Maiss, Edgar; Varrelmann, Mark (Frontiers in Plant Science, 2020)
Beet necrotic yellow vein virus (BNYVV) is causal agent of rhizomania disease, which is the most devastating viral disease in sugar beet production leading to a dramatic reduction in beet yield and sugar content. The virus is transmitted by the ubiquitous distributed soil-borne plasmodiophoromycete Polymyxa betae that infects the root tissue of young sugar beet plants. Rz1 is the major resistance gene widely used in most sugar beet varieties to control BNYVV. The strong selection pressure on the virus population promoted the development of strains that can overcome Rz1 resistance. Resistance-breaking has been associated with mutations in the RNA3-encoded pathogenicity factor P25 at amino acid positions 67-70 (tetrad) as well as with the presence of an additional RNA component (RNA5). However, respective studies investigating the resistance-breaking mechanism by a reverse genetic system are rather scarce. Therefore, we studied Rz1 resistance-breaking in sugar beet using a recently developed infectious clone of BNYVV A-type. A vector free infection system for the inoculation of young sugar beet seedlings was established. This assay allowed a clear separation between a susceptible and a Rz1 resistant genotype by measuring the virus content in lateral roots at 52 dpi. However, mechanical inoculation of sugar beet leaves led to the occurrence of genotype independent local lesions, suggesting that Rz1 mediates a root specific resistance towards BNYVV that is not active in leaves. Mutation analysis demonstrated that different motifs within the P25 tetrad enable increased virus replication in roots of the resistant genotype. The resistance-breaking ability was further confirmed by the visualization of BNYVV in lateral roots and leaves using a fluorescent-labelled cDNA clone of RNA2. Apart from that, reassortment experiments evidenced that RNA5 enables Rz1 resistance-breaking independent of the P25 tetrad motif. Finally, we could identify a new resistance-breaking mutation, which was selected by high-throughput sequencing of a clonal virus population after one host passage in a resistant genotype. Our results demonstrate the feasibility of the reverse genetic system for resistance-breaking analysis and illustrates the genome plasticity of BNYVV allowing the virus to adapt rapidly to sugar beet resistance traits.